KELAYAKAN EKONOMI USAHA PERIKANAN TANGKAP DENGAN PENGILAR DI PERAIRAN TAWAR KABUPATEN KUTAI KARTANEGARA - Sulistianto, Erwan; Fahrizal, Wahyu (Universitas Dharmawangsa, 2024)
Kutai Kartanegara Regency is one of the regencies located in East Kalimantan Province. Geographically, Kutai Kartanegara Regency is traversed by the Mahakam River, Semayang Lake, and Melintang Lake. These conditions support fishing activities carried out by fishermen living around the river and lakes. The aim of this research is to analyze the feasibility of fishing businesses using traps. The research took place from March to June 2024. Sampling was done through purposive sampling, with 30 fishermen using pengilar as respondents. The data analysis methods used were descriptive analysis and Revenue Cost Ratio (R/C) analysis. The research findings indicate that the fishing business has been profitable and is viable for fishermen to continue. The profit obtained is Rp 29,536/trip with an R/C of 1.32.